NNT is a key regulator of adrenal redox homeostasis and steroidogenesis in male mice. Issue 1 (January 2018) - Meimaridou, E; Goldsworthy, M; Chortis, V; Fragouli, E; Foster, P A; Arlt, W; Cox, R; Metherell, L A
Abstract : Nicotinamide nucleotide transhydrogenase, NNT, is a ubiquitous protein of the inner mitochondrial membrane with a key role in mitochondrial redox balance. NNT produces high concentrations of NADPH for detoxification of reactive oxygen species by glutathione and thioredoxin pathways. In humans, NNT dysfunction leads to an adrenal-specific disorder, glucocorticoid deficiency. Certain substrains of C57BL/6 mice contain a spontaneously occurring inactivating Nnt mutation and display glucocorticoid deficiency along with glucose intolerance and reduced insulin secretion. To understand the underlying mechanism(s) behind the glucocorticoid deficiency, we performed comprehensive RNA-seq on adrenals from wild-type (C57BL/6N), mutant (C57BL/6J) and BAC transgenic mice overexpressing Nnt (C57BL/6J BAC ). The following results were obtained. Our data suggest that Nnt deletion (or overexpression) reduces adrenal steroidogenic output by decreasing the expression of crucial, mitochondrial antioxidant ( Prdx3 and Txnrd2 ) and steroidogenic ( Cyp11a1 ) enzymes. Pathway analysis also revealed upregulation of heat shock protein machinery and haemoglobins possibly in response to the oxidative stress initiated by NNT ablation. In conclusion, using transcriptomic profiling in adrenals from three mouse models, we showed that disturbances in adrenal redox homeostasis are mediated not only by under expression of NNT but also by its overexpression. Further, we demonstrated that both under expression or overexpression of NNT reduced corticosterone output implying a central role for it in the control of steroidogenesis. This is likely due to a reduction in the expression of a key steroidogenic enzyme, Cyp11a1, which mirrored the reduction in corticosterone output.